Business cooperating with vocational education and training providers for quality skills and attractive futures - Vroonhof, Paul [Verfasser]; Durazzi, Niccolo [Verfasser]; Secher, Johan [Verfasser]; Stoumann, Jakob [Verfasser]; Broek, Simon [Verfasser]; Haan, Laura de [Verfasser]; Ende, Inge van den [Verfasser]; Loo, Simon van [Verfasser] (Education Information Network in the European Union, 2017)
"This study analyses examples of cooperation between vocational education and training (VET) and businesses. In addition to the 12 selected case studies, it builds on expert interviews and a desk research component. Three dimensions have been identified to classify VET-business cooperation: (1) the VET process (curriculum development, VET delivery, feedback loop); (2) the topics of cooperation (matching supply and demand, work-based learning, digital skills, innovation - including digitalisation aspects not related to skills development, entrepreneurial skills, mobility, social inclusion, raising awareness); and (3) the level of cooperation (individual, local/regional, sectoral, national, European, global). Initiatives such as dual study programmes in Germany or the VET programme developed by the Danish retail chain Coop show how VET-business cooperation influences the quality and attractiveness of VET." The study was commissioned by the European Commission, Directorate General Employment and Social Affairs. (Author's abstract, BIBB-Doku)
Keywords: S 2.4.1 Lernortkooperation; S 1.4 Hochschulbildung; I 1 Internationale Berufsbildung; I 2.2 Europa; Privatwirtschaft; Unternehmen; Kooperation; Berufsbildung; Lernortkooperation; Public-private-Partnership; Dualer Studiengang; Internationale Zusammenarbeit; Europäische Union